Titrimetric and Spectrophotometric Determination of Metaprolol tartrate in Pharmaceuticals Using N-Bromosuccinimide - K. Basavaiah; B. C. Somashekar (E-Journal of Chemistry)
One titrimetric and two spectrophotometric methods are presented for the assay of metaprolol tartrate (MPT) in bulk drug and in tablets. The methods employ N-bromosuccinimide (NBS) as the oxidimetric reagent and two dyes, methyl orange and indigo carmine as spectrophotometric reagents. In titrimetry, an acidified solution of MPT is treated with a known excess amount of NBS and after a definite time, the unreacted oxidant is determined by iodometric back titration. Spectrophotometry involves adding a measured excess of NBS to MPT in acid medium followed by determination of residual NBS by reacting with a fixed amount of either methyl orange and measuring the absorbance at 520 nm (Method A) or indigo carmine and measuring the absorbance at 610 nm (Method B). In all the methods, the amount of NBS reacted corresponds to the amount of MPT. Reaction conditions have been optimized. Titrimetry allows the determination of 1 - 12 mg of MPT and the calculations are based on a 1: 4 (MPT: NBS) reaction stoichiometry. In spectrophotometry, the measured absorbance is found to increase linearly with the concentration of MPT serving as basis for quantitation. The systems obey Beer’s law for 0.5 - 4.0 μg mL-1 and 1.25 - 10.0 μg mL-1 for method A and method B, respectively. The apparent absorptivities are calculated to 1.07 × 105 be and 4.22 × 104 L mol cm-1 for method A and method B, respectively. The methods developed were applied to the assay of MPT in commercial tablet formulations, and the results were compared statistically with those of a reference method. The accuracy and reliability of the methods were further ascertained by performing recovery tests via standard-addition method.